The model of allotments booking in a shuttle train - Jaržemskis, Andrius (Transport, 2005)
The article presents the model of allotments booking for trucks or containers in shuttle trains. This model could be used in practice if railway companies sale free allotments in rolling stock for forwarders. This paper proposes a stochastic dynamic programming model of a short‐term capacity planning model for necessary allotment. The allotment could be acquired by freight forwarders many months ahead on a contract basis, but usually the forecast demand is unreliable. The preplanning of allotment for transport units is needed when the date draws nearer to the train departure time. The presented model evaluates the optimal cost policy based on economic trade‐off between the cost of backlogged shipment and the cost of acquiring additional allotment. First Published Online: 27 Oct 2010